THE ROLE OF INDIVIDUAL AND CONTEXTUAL FACTORS ON THE EMERGENCE OF EMPLOYEES’ VOICE BEHAVIOR - Ibrahim, Muhammad; Andiyasari, Andin; Riantoputra, Corina D. (Jurnal Psikologi, 2020)
The purpose of the study is to examine the impact of individual (power distance orientation) and contextual (perceived organizational support) factors on voice behavior. The study utilized online survey method using google form on 103 employees in DKI Jakarta and its surrounding areas using a measuring instrument with reliability between .77-.81. The results of moderated regression analysis found that (1) power distance orientation has a negative effect on voice behavior; (2) perceived organizational support as a moderator has imperative role in explaining the relationship between power distance orientation and voice behavior. Perceived organizational support strengthens the negative relationship between power distance orientation and voice behavior. This study explained 38% of the formation of voice behavior. High perceived organizational support became significant factor in strengthening employees with low power distance orientation to exhibit voice behavior. The study was revealed the interaction between power distance orientation, perceived organizational support, and voice behavior.